Clinical and angiographic outcomes of axial stent deformations in unrestricted real world patient population. (20th September 2017) - Sabbah, Mahmoud; Kadota, Kazushige; Kubo, Shunsuke; Hyodo, Yusuke; Otsuru, Suguru; Hasegawa, Daiji; Tada, Takeshi; Habara, Seiji; Tanaka, Hiroyuki; Fuku, Yasushi; Goto, Tsuyoshi
Abstract : Background: Prior reports have suggested that the design of the Promus Element stent is prone to longitudinal stent deformation (LSD). However, little is known about the clinical and angiographic outcomes of Promus Element stent axial deformations when implanted in unrestricted coronary lesions. Method and Results: Two independent reviewers retrospectively evaluated the procedure steps of 961 Promus Element stent (833 de novo lesions in 494 consecutive patients) implanted in unrestricted coronary lesions, between February 2012 and March 2013, and compared the prevalence, predictors, and the mid‐term clinical and angiographic outcomes between lesions with and without stent deformation. Fifteen stents (1.56%) with LSD were observed (95% confidence interval [CI]: 0.78–2.34%). The proximal edge of the stent was deformed in 13 stents (86.6%). Ostial stenting (Adjusted Odds ratio [OR]: 9; 95%CI: 2.27–33.3; P  = 0.002), and bifurcation lesions (Adjusted OR: 3; 95%CI: 1.03–8.8; P  = 0.04) were independently associated with the occurrence of stent deformation. LSD led to unplanned stenting in (53%, 8 of 15) of the deformed stents, which consumed larger contrast volume and longer fluoroscopy time. At 8‐month follow‐up, there was no significant difference in binary restenosis rate and target lesions revascularization between both groups ( P  = 0.98, and P  = 0.56, respectively), while death occurred in six patients of the non‐LSD group (1.36%, 6 of 440) and none in the LSD group. All patients of the LSD group had no major adverse clinical events at 8‐month follow‐up. Conclusions: Axial stent deformation in Promus Element platform is an infrequent event, occurs following manipulation of the interventional tools. Other than unplanned stenting, the LSD was not associated with any adverse clinical events at 8‐month follow‐up.